Optimalisasi Pengawasan Peredaran Obat Dan Makanan Dalam Rangka Perlindungan Kesehatan Masyarakat - Arief Handoko Usman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The distribution of safe and quality drugs is a key factor in maintaining public health. However, complex challenges related to the distribution of illegal, counterfeit and unsafe drugs, as well as drug abuse, require efforts to control the distribution of drugs and food.With 250 million people, Indonesia has become a potential target for drug and food marketing both in person and online.The results of the study show that optimizing drug circulation control is a fundamental pillar in protecting public health. By improving the quality of monitoring the distribution of drugs and food, strengthening BPOM institutions as well as socializing and educating the public, it is hoped that this will ensure the quality of drug distribution in food to protect public health.